Promising applicable heterometallic Al2O3/PbO2 nanoparticles in shielding properties - Ali, Atif Mossad; Issa, Shams A. M.; Ahmed, Mohamed Rashad; B. Saddeek, Yasser; Mohd Zaid, Mohd Hafiz; Sayed, Mahmoud; Somaily, Hamoud H.; Tekin, Huseyin Ozan; Sidek, Ab Aziz; Matori, Khamirul Amin; Zakaly, Hesham M. H. (Elsevier, 2020)
Hetrometal oxides of (1 − x)Al2O3/xPbO2 (NPs) nanoparticles with different PbO2 content (x = 0, 0.3, 0.4, 0.5, 0.6 and 0.7) have been prepared by irradiation method. The NPs powder has been checked by X-ray diffraction (XRD). XRD measurements affirmed the presence of both pure NPs and nanocomposites of (1 − x)Al2O3/xPbO2 NPs with different PbO2 contents. The calculated structural parameters which using the experimental result of XRD charts to give a complete image of these measurements. Moreover, the results using FLUKA code showed that the values attenuation coefficient (μm), high effective atomic number (Zeff) and neutron shielding parameters increase as the lead dioxide increase in the Al2O3/PbO2 samples. While the values of half-value layer (HVL) and mean free path (MFP) decrease with increasing PbO2 content. The investigated shielding features of the chosen Al2O3/PbO2 would be advantageous for exposure control.